Graphene/MoS2/FeCoNi(OH)x and Graphene/MoS2/FeCoNiPx multilayer-stacked vertical nanosheets on carbon fibers for highly efficient overall water splitting - Xixi Ji (Nature Portfolio, 2021)
While water-splitting electrocatalysis offers a renewable means for carbon-neutral energy production, it is a challenge to design efficient, active, and stable catalysts. Here, authors prepare multilayer composite nanosheet materials as bifunctional water-splitting electrocatalysts.